The inotropic peptide βARKct improves βAR responsiveness in normal and failing cardiomyocytes through G(βγ)-mediated L-type calcium current disinhibition. - Völkers, Mirko; Weidenhammer, Christian; Herzog, Nicole; Qiu, Gang; Spaich, Kristin; von Wegner, Frederic; Peppel, Karsten; Müller, Oliver J.; Schinkel, Stefanie; Rabinowitz, Joseph E.; Hippe, Hans-Jörg; Brinks, Henriette; et al. (Circulation Research, 2011)
RATIONALE The G(βγ)-sequestering peptide β-adrenergic receptor kinase (βARK)ct derived from the G-protein-coupled receptor kinase (GRK)2 carboxyl terminus has emerged as a promising target for gene-based heart failure therapy. Enhanced downstream cAMP signaling has been proposed as the underlying mechanism for increased β-adrenergic receptor (βAR) responsiveness. However, molecular targets mediating improved cardiac contractile performance by βARKct and its impact on G(βγ)-mediated signaling have yet to be fully elucidated. OBJECTIVE We sought to identify G(βγ)-regulated targets and signaling mechanisms conveying βARKct-mediated enhanced βAR responsiveness in normal (NC) and failing (FC) adult rat ventricular cardiomyocytes. METHODS AND RESULTS Assessing viral-based βARKct gene delivery with electrophysiological techniques, analysis of contractile performance, subcellular Ca²(+) handling, and site-specific protein phosphorylation, we demonstrate that βARKct enhances the cardiac L-type Ca²(+) channel (LCC) current (I(Ca)) both in NCs and FCs on βAR stimulation. Mechanistically, βARKct augments I(Ca) by preventing enhanced inhibitory interaction between the α1-LCC subunit (Cav1.2α) and liberated G(βγ) subunits downstream of activated βARs. Despite improved βAR contractile responsiveness, βARKct neither increased nor restored cAMP-dependent protein kinase (PKA) and calmodulin-dependent kinase II signaling including unchanged protein kinase (PK)Cε, extracellular signal-regulated kinase (ERK)1/2, Akt, ERK5, and p38 activation both in NCs and FCs. Accordingly, although βARKct significantly increases I(Ca) and Ca²(+) transients, being susceptible to suppression by recombinant G(βγ) protein and use-dependent LCC blocker, βARKct-expressing cardiomyocytes exhibit equal basal and βAR-stimulated sarcoplasmic reticulum Ca²(+) load, spontaneous diastolic Ca²(+) leakage, and survival rates and were less susceptible to field-stimulated Ca²(+) waves compared with controls. CONCLUSION Our study identifies a G(βγ)-dependent signaling pathway attenuating cardiomyocyte I(Ca) on βAR as molecular target for the G(βγ)-sequestering peptide βARKct. Targeted interruption of this inhibitory signaling pathway by βARKct confers improved βAR contractile responsiveness through increased I(Ca) without enhancing regular or restoring abnormal cAMP-signaling. βARKct-mediated improvement of I(Ca) rendered cardiomyocytes neither susceptible to βAR-induced damage nor arrhythmogenic sarcoplasmic reticulum Ca²(+) leakage.
Keywords: βARKct; β-adrenergic receptor; L-type Ca2+ channel; G proteins